“Don’t Be Frightened Dear … This Is Hollywood”: British Filmmakers in Early American Cinema - Ian Scott (European Journal of American Studies)
British visitors to Hollywood from the late 1920s onward have captured the attention of writers as importing a particular view of their home country in a succession of ”British-Hollywood” movies. This article argues, however, that there was an initial wave of such trans-national pioneers – writer-directors Charles Brabin, Colin Campbell, Reginald Barker and Frank Lloyd – who not only did not demonstrate such “Britishness” in their work but instead made a crucial contribution to the development of classical Hollywood filmmaking. At times, they also offered a more nuanced view of social and historical complexities of the American past than many US-born directors.